Re-Discovering Diaghilev's Pas d'Acier - Sayers, Lesley-Anne 1958-2010 (Edinburgh: Edinburgh University Press, 2000)
RESUMEN: This article is drawn from PhD research (Bristol University 1999) into Georgii Yakulov's scenic designs for the Diaghilev Ballets Russes production of Le Pas d'Acier (Prokofiev, Yakulov, Massine 1927). This study involved a reconstruction, in model form, currently on exhibition at the Palais de Centenaire in Brussels, shown in the photographs below. The purpose of this reconstruction was to explore the design, within the limitations of a model, using simple lighting to give an indication of the use of gauze and kinetic set parts.